2010
DOI: 10.1051/0004-6361/201014562
|View full text |Cite
|
Sign up to set email alerts
|

Silicon in the dust formation zone of IRC +10216

Abstract: The interstellar medium is enriched primarily by matter ejected from evolved low and intermediate mass stars. The outflows from these stars create a circumstellar envelope in which a rich gas-phase and dust-nucleation chemistry takes place. We observed the nearest carbon-rich evolved star, IRC +10216, using the PACS (55−210 μm) and SPIRE (194−672 μm) spectrometers on board Herschel. We find several tens of lines from SiS and SiO, including lines from the v = 1 vibrational level. For SiS these transitions range… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 30 publications
8
48
0
Order By: Relevance
“…The more recent study of Decin et al (2010a), based on observations with SPIRE and PACS that are particularly sensitive to the warm inner envelope, reports a SiS abundance of 4 × 10 −6 , in good agreement with our finding for the inner layers.…”
Section: Molecular Abundancessupporting
confidence: 92%
See 1 more Smart Citation
“…The more recent study of Decin et al (2010a), based on observations with SPIRE and PACS that are particularly sensitive to the warm inner envelope, reports a SiS abundance of 4 × 10 −6 , in good agreement with our finding for the inner layers.…”
Section: Molecular Abundancessupporting
confidence: 92%
“…ISO observed a full infrared scan from 2.4 to 197 μm, albeit with a low spatial and spectral resolution, that probed the inner layers of IRC +10216 through the lines of abundant molecules such as CO, C 2 H 2 , and HCN (Cernicharo et al 1996(Cernicharo et al , 1999. More recently, spectral surveys carried out with Herschel with a high angular resolution have detected many high energy rotational transitions of molecules such as CO, HCN, CS, SiS, SiO, and SiC 2 , at low spectral resolution using SPIRE and PACS in the 55−672 μm range (Decin et al 2010a), and at high spectral resolution in the 488−1901 GHz range covered by HIFI .…”
Section: Introductionmentioning
confidence: 99%
“…The dust nucleation zone starts around 5 R (or 100-150 mas, Decin et al 2010b). This is similar to the resolution of these images, but we cannot distinguish faint details this close to the strong stellar peak.…”
Section: Stellar and Dust Propertiessupporting
confidence: 76%
“…To test our results, we assess the mass of AC dust that can grow from the C 6 H 6 and C 2 H 2 masses in the radius range of interest, compare the derived AC mass to the gas mass, and derive dust-to-gas mass ratios. It has been found that IRC+10216 is heavily dust-rich and has a dust-to-gas mass ratio comprised between 1.4 × 10 −3 and 4 × 10 −3 based on various studies (e.g., Ivezić & Elitzur 1996;Groenewegen 1998;Decin et al 2010a). In Table 5, we list the abundances and total masses of C 2 H 2 and C 6 H 6 formed as a function of radius.…”
Section: Carbon Dust Precursors: Hydrocarbons and Aromaticsmentioning
confidence: 99%